Leiomyoma of vulva mimmicking bartholin cyst - Singh, Anju; Goel, Bharti; Takkar, Navneet; Jain, Ekta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Leiomyoma of vulva are uncommon findings in women of reproductive age group. It is often misdiagnosed as Bartholin cyst as unilateral swelling of vulva in women of reproductive age group is commonly a bartholin cyst or abscess. We describe a case of leiomyoma that clinically mimicked bartholin duct cyst. Identification of leiomyoma or leiomyosarcoma is necessary because of risk of recurrence, need of radiation and or chemotherapy in addition to surgical excision whereas standard treatment for bartholin cyst is marsuplisation.